Durability and swelling of tropical stabilized peat soils - Deboucha, S.; Hashim, Roslan (2009)
This research describes a study on peat soil stabilisation to improve its physical and engineering properties. It investigates the effect of additives (binder amount 5, 10 and 15 (85 cement, 15 bentonite) and range of sand 5 to 25 on the index properties as well as, durability, plasticity and swelling of tropical peat soils. The amount of additives added to the peat soil sample was investigated in terms of the percentage of the dry soil mass. The results showed that of the additive admixtures altered the engineering properties of tropical peat soils. The soil plastic limit, liquid limit and plastic index were found to decrease with increase of the additive content. Swelling of stabilized peat soils was found decrease with increase additives, however, the curing time. The effect of durability increased resistance of strength for lower content of addition to higher content additives.